Fine Needle Aspiration Cytology of Giant Cell Tumour of Tendon Sheath - Sonam Jain; Saumya Nanda; Malvika Shastri; Annu Nanda; Vaibhav Garg (Journal of Clinical and Diagnostic Research, 2022)
Introduction: Giant Cell Tumour of Tendon Sheath (GCTTS), also known as localised nodular tenosynovitis, is a slow growing benign soft tissue tumour arising from synovium of tendon sheath, bursa or joint. Clinically, the lesions occur as skin-coloured nodules typically on the extremities. These tumours occur more frequently on the upper limbs especially hands (77%) where they form the second most common tumour following simple ganglion cyst. Aim: To describe the cytomorphologic findings in GCTTS and their histopathological features. Materials and Methods: This retrospective study was conducted at Department of Pathology, ESI Hospital, New Delhi, India, in 12 diagnosed GCTTS cases for their cytological features from January 2015 to December 2017. Fine Needle Aspiration Cytology (FNAC) was performed with a 22-gauge needle attached to a 10 mL syringe. Smears were air-dried and stained with Giemsa stain. Cytomorphology of all the selected cases were analysed and descriptive statistics were used to evaluate the cases. Results: A total of 12 cases of GCTTS were retrieved. Diagnosis of GCTTS was made by FNAC in all the cases and confirmed by histopathological examination in half of the cases. The mean age of presentation was 39 years. Of these, 8 (66.67%) were women and 4 (33.33%) were men. The lesions were found most commonly over the index finger (n=5) followed by the ring finger (n=3), thumb (n=2), middle finger (n=1) and little finger (n=1). The most frequent clinical presentation was a painless, nodular, slow growing firm swelling over the finger. FNAC revealed cellular smears with few clusters and numerous scattered stromal cells along with interspersed multinucleated giant cells. Conclusion: A definitive preoperative diagnosis of GCTTS obtained through FNAC helps in formulating appropriate treatment plan. Histopathologic examination will confirm the cytological diagnosis and can help to predict recurrence by providing information on the resection margin, any satellite nodules, variable cell types and mitotic activity.